Parkinson's Disease - Understanding Pathophysiology and Developing Therapeutic Strategies 2018
DOI: 10.5772/intechopen.73520
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders in Parkinson’s Disease

Abstract: Sleep disorders in Parkinson's disease (PD) are common. They can develop due to many factors. PD symptoms like rigidity or tremor, some PD medications, restless legs syndrome, depression, nocturia, and degenerative changes in the brainstem can cause sleep disorders in PD. Sleep disorders in PD may occur during the day or at night. Sleep disorders can occur before or during the disease. Sleep disorders can impair patients' quality of life and worsen their symptoms. For this reason, it is very important to recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…There have been several studies that have shown that subjects with PD exhibit unique EEG biomarkers including decreased β and γ (> 35 Hz) powers [6,7], slowing of resting-state oscillatory brain activity [8,9] and significant changes in phase-amplitude coupling when compared to healthy controls (HC) [10,11]. Patients with PD frequently experience sleep disorders, including insomnia, rapid eye movement (REM) sleep behavior disorder (RBD), and excessive daytime sleepiness [12,13]. In addition, PD is characterized by alterations in sleep architecture, including reductions in REM sleep which plays a vital role in consolidating procedural memory and motor skills [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies that have shown that subjects with PD exhibit unique EEG biomarkers including decreased β and γ (> 35 Hz) powers [6,7], slowing of resting-state oscillatory brain activity [8,9] and significant changes in phase-amplitude coupling when compared to healthy controls (HC) [10,11]. Patients with PD frequently experience sleep disorders, including insomnia, rapid eye movement (REM) sleep behavior disorder (RBD), and excessive daytime sleepiness [12,13]. In addition, PD is characterized by alterations in sleep architecture, including reductions in REM sleep which plays a vital role in consolidating procedural memory and motor skills [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PD is characterized by alterations in sleep architecture, including reductions in REM sleep which plays a vital role in consolidating procedural memory and motor skills [14]. Recent studies have shown that both REM and non-REM (NREM) sleep exhibit unique features in PD and PD with dementia as compared to healthy controls (HC), including lower stability, higher slowing ratio, an increase in spectral power in the δ (1-4 Hz) and θ (4-8 Hz) bands during REM, as well as lower baseline power in σ waves (12)(13)(14)(15) within the parietal regions during the NREM sleep stages [15][16][17][18][19]. Since patients with PD have both cognitive and motor dysfunction, alterations in sleep stages have potential clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Gait disturbance, in particular, is one of the most commonly reported symptoms which manifests as impaired gait speed, increased movement variability, movement asymmetry, and reduced step length (Mirelman et al, 2019). Moreover, PD is associated with non-motor symptoms such as autonomic dysfunction, psychiatric disorders, and sleep disorders (Aygun, 2018). Autonomic dysfunction is commonly observed as cardiovascular symptoms such as hypertension or hypotension, or as gastrointestinal symptoms such as constipation, urinary complications, and sexual dysfunction (Asahina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%